2018
DOI: 10.1097/moh.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage pathways and B-cell lymphomagenesis

Abstract: Purpose of review Recent lymphoma genome sequencing projects have shed light on the genomic landscape of indolent and aggressive lymphomas, as well as some of the molecular mechanisms underlying recurrent mutations and translocations in these entities. Here, we review these recent genomic discoveries, focusing on acquired DNA repair defects in lymphoma. In addition, we highlight recently identified actionable molecular vulnerabilities associated with recurrent mutations in chronic lymphocytic leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…In summary, this review indicates the potential opportunities to combine C-NHEJ and A-EJ inhibitors with chemoradiation treatment modalities for inducing synthetic lethal vulnerability in hematologic malignant cells with up-regulation of these pathways. [203,225] MV4-11 cells (AML cell line) ATM inhibition radiosensitized MV4-11 leukemia cells [182] P39 and MOLM-13 cell lines (MDS cell lines) ATM inhibition increase radiosensitization of MDS cells [182] EBV-driven Burkitt lymphoma cells Inhibition of EBV replication through inhibition of KAP1 phosphorylation [205] Ramos cells Prevention of ATM auto-phosphorylation and potentiation of etoposide-induced apoptosis [226] Cisplatin-resistant MCL cell line (JeKo-1/DDP) Enhanced cisplatin-induced DNA damage [206] HCL cell line MLMA Induction of apoptosis through inhibiting NF-κB pathway [207] KU-59403 Jurkat cells Showing higher potency, tissue distribution, and efficacy over KU-55933 [225] AZD0156 AML exhibits therapeutic potential in a mouse model of MLL-rearranged AML [227] KU-60019 Human B cell lymphoma cell lines, lymphoblastoid cell lines, and myeloma lines KU-60019 potentiates bendamustine activity [212] MCL cell lines KU60019 synergizes the antineoplastic effect of romidepsin [228] Caffeine (Inhibitor of both ATM and ATR)…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, this review indicates the potential opportunities to combine C-NHEJ and A-EJ inhibitors with chemoradiation treatment modalities for inducing synthetic lethal vulnerability in hematologic malignant cells with up-regulation of these pathways. [203,225] MV4-11 cells (AML cell line) ATM inhibition radiosensitized MV4-11 leukemia cells [182] P39 and MOLM-13 cell lines (MDS cell lines) ATM inhibition increase radiosensitization of MDS cells [182] EBV-driven Burkitt lymphoma cells Inhibition of EBV replication through inhibition of KAP1 phosphorylation [205] Ramos cells Prevention of ATM auto-phosphorylation and potentiation of etoposide-induced apoptosis [226] Cisplatin-resistant MCL cell line (JeKo-1/DDP) Enhanced cisplatin-induced DNA damage [206] HCL cell line MLMA Induction of apoptosis through inhibiting NF-κB pathway [207] KU-59403 Jurkat cells Showing higher potency, tissue distribution, and efficacy over KU-55933 [225] AZD0156 AML exhibits therapeutic potential in a mouse model of MLL-rearranged AML [227] KU-60019 Human B cell lymphoma cell lines, lymphoblastoid cell lines, and myeloma lines KU-60019 potentiates bendamustine activity [212] MCL cell lines KU60019 synergizes the antineoplastic effect of romidepsin [228] Caffeine (Inhibitor of both ATM and ATR)…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The promoting effect of DNA-PK inhibitors on radiation and topoisomerase II inhibitors has been demonstrated in several hematologic cancers, such as CLL, ALL, CML, AML, APL, and adult T-cell leukemia/lymphoma [ 181 ]. Given the relationship between ATM deficiency and sensitivity to DNA-PKcs inhibitors, the effects of these inhibitors on lymphoma have been investigated [ 182 ].…”
Section: Introductionmentioning
confidence: 99%
“…DLBCL is a heterogeneous disease characterized by high levels of genomic instability (Barlow et al, 2013), and activation of DNA damage repair pathways, including the activation of nucleotide excision DNA repair (NER) and DNA damage response kinases (Shaheen et al, 2011;Gu et al, 2015). Studies have shown that inhibition of the process of DNA damage repair, such as inhibitors of kinase WEE1, could effectively prevent the progress of DLBCL (Knittel et al, 2018;Jong et al, 2020). Furthermore, it has been demonstrated that NER pathway related proteins were usually overexpressed in CHOP (Cyclophosphamide, Doxorubicin, Vincristine and Prednisone) resistant DLBCL cells.…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in Fig. 1, there are multiple mechanisms by which DDR pathways are deregulated in B-cell lymphomas [23]. The vast majority of lymphomas derive from germinal center (GC) B-cells or Bcells that have passed through the GC [24].…”
Section: Ddr and Lymphomasmentioning
confidence: 99%